The Profiles of Stevens-Johnson Syndrome (SJS) and Toxic Epidermal Necrolysis (TEN) Patients in Tertiary Hospital - William Andrew Isaac; Damayanti Damayanti; Nurmawati Fatimah; Afif Nurul Hidayati (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2021)
Background: Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are severe eruptive skin reactions that can cause death. The incidence of SJS and TEN cases in the United States is 1.5–9.6 per 1,000,000 per year. Drugs are the primary etiology of SJS and TEN. Some drugs are at high risk and used frequently. The SJS and TEN mortality rates were relatively high, with SJS 4.8%, SJS / TEN overlap 19.8%, and TEN 14.8%. In Indonesia, there are lack of studies on the SJS and TEN. This study is needed to determine the epidemiological profile of SJS and TEN. Purpose: This study aimed to describe SJS and TEN patients' profiles. Methods: Drug-induced SJS and TEN cases from January 2016 to December 2019 were evaluated from the medical records patients' profile, incidence, suspected drugs, risk factors, and comorbidities of SJS and TEN were described. Result: There were 28 SJS and TEN patients, comprising of 24 SJS patients (85.7%), 3 TEN patients (10.7%), and 1 SJS overlapping TEN patients (3.5%). The most common suspected drugs were paracetamol (22.2%), carbamazepine (20.4%), cefadroxil (8.8%), and ciprofloxacin (8.8%). Women (53.5%) experienced more severe drug eruptions than men (46.4%). The largest age group was 25–44 years (35.7%). Most comorbidities were epilepsy (21%), diabetes (15.7%), hypertension (15.7%), and stroke (15.7%). Conclusion: The most common manifestation was SJS with paracetamol as the most common suspected drug, followed by carbamazepine.